Pengembangan Modul Pembelajaran Praktikum Berbasis Literasi Sains pada Materi Sifat Benda dan Perubahannya di Kelas V MI Babul Ulum Kanten - Runasih, Runasih; Yulia, Nurul Mahruzah; Amreta, Midya Yuli (Institut Agama Islam Negeri (IAIN) Curup, 2023)
One of the reasons for the low scientific literacy abilities of students in Indonesia is the use of learning media that does not contain elements of scientific literacy. Learning carried out directly using practical learning modules can improve students' scientific literacy skills. This research aims to explain the development process and results of developing practical learning modules based on scientific literacy. The research and development method used by researchers is Research and Development using the ADDIE model which includes the Analyze, Design, Development, Implementation and Evaluation stages developed by Robert Maribe Branch. The instruments used in this research and development are observation sheets, interview sheets, media, material and language expert validation questionnaires, student response questionnaires and tests. The results of research and development of practical learning modules based on scientific literacy obtained an average validation score from media, material and language experts of 88%, media experts 92%, material experts 85% and language experts 87%. The small scale student response questionnaire got 82% results, and the large scale student response questionnaire got 91% results from 18 students. The result of calculating the N-Gain score is 0.879, which shows that the practical learning module based on scientific literacy is very effectively applied in learning.